PARKINSON’S DISEASE – PATHOGENESIS, CLINICAL FEATURES, AND DIAGNOSTIC STRATEGIES - Khakimov M.N. (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by motor and non-motor symptoms that significantly impair quality of life. The disease results primarily from degeneration of dopaminergic neurons in the substantia nigra pars compacta and the presence of intracellular α-synuclein aggregates known as Lewy bodies. This article reviews current understanding of the molecular mechanisms, clinical manifestations, and diagnostic approaches in Parkinson’s disease.